Prepositioner i finskspråkiga gymnasisters inlärarsvenska - Juurakko, Taina (1996)
The present study investigates how the Finnish learners use prepositions in their Swedish interlanguage and what kinds of errors they make in using them. The data consist of essays written by pupils in the 1st and 3rd grades of the Finnish secondary school. This material has been compared with essays written by Swedish secondary school pupils and with the frequencies of prepositions in the textbooks used in Finnish schools. The research method is a quantitative one, but also qualitative analysis has been carried out. The method used combines ideas from contrastive analysis, error analysis, performance analysis, functional analysis and transfer analysis. The analysis shows that Finnish learners use fewer prepositions than the Swedish learners. They do not have as many different prepositions in their interlanguage and they use the most common prepositions more often than the Swedes. In the 1st grade the pupils use prepositions in different functions than in the 3rd grade. The concrete functions, local as well as temporal, are very common in the 1st grade, whereas pupils in the 3rd grade use several prepositions in connection with verbs. This suggests that the concrete functions are learnt earlier than the more abstract ones. Prepositions are difficult for both learner groups. The older learners have a better command of almost every preposition and every function than the younger ones. However, the difference is significant only in some cases. The errors have been divided into three categories: incorrect use, overuse and underuse. The difference between the two groups is that the more advanced learners know better than the younger ones which preposition to choose in a special context, whereas over- and underuse of prepositions is typical of both groups of learners. The temporal prepositions are the most difficult ones in non-obligatory contexts, where the errors are evidence for overuse. In obligatory contexts, where errors are a sign of underuse, the prepositions which are used with verbs are the most difficult ones. Statistical analysis shows that transfer from Finnish can explain some errors, but there is also influence from L2. Sometimes these influences cannot be separated, in other cases it is possible to tell whether it is L1- or L2-influence that is stronger.